EMPOWERING OTHERS IN SALESTEAM KNOWLEDGE CONVERSION: A STRATEGY TO BOOST SELLING PERFORMANCE - Sudarti, Ken (UNISSULA, 2021)
This study aims to examine the role of empowering others on knowledge conversion in improving selling performance. Empowering others on knowledge conversion is the spirit of salesmen who are members of a sales team to ask and help colleagues to be willing and able to do the best knowledge conversion activities. This study used 193 sharia insurance salespeople as respondents in Indonesia. The regression model is used to analyze the data and test the empirical model. Empowering others on knowledge conversion has proven to improve the selling performance of sharia insurance salespeople in Indonesia. The concept of empowering others on knowledge conversion is a critical reconstruction of needs for achievement theory and social capital theory through the internalization of Islamic values. Through empowering others in doing knowledge conversion, salespeople who are members of the sales team will have updated sales knowledge to achieve the best performance.